THE STATE OF LAW AND DEMOCRACY: THE REALITY OF STATE IN THE CONSTITUTIONAL SYSTEM IN INDONESIA - Husni Thamrin; Muhammad Arganata Thamrin; Muhammad Husni Fahrudin; Leonito Ribeiro (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
Indonesia constitutionally affirms itself as a state based on law (rechtsstaat), but in practice, tensions often arise between the supremacy of law and political interests. This article aims to analyze the dialectical relationship between the concept of the rule of law and democracy in the Indonesian constitutional system, particularly in the context of post-2024 election dynamics. Using a normative legal approach and an analysis of responsive legal typology by Philippe Nonet and Philip Selznick, this study finds that law enforcement in Indonesia still faces major challenges in the form of legal politicization, the weakening of independent institutions, and a shift towards semantic constitutionalism. This study concludes that strengthening constitutional democracy requires the integration of responsive law, strong political ethics, and constitutional adaptation to digital disruption to maintain genuine popular sovereignty.